SPEECH ERRORS OF GIRL ENVIRONMENT ACTIVIST’S SPEECH IN PLASTIC HEALTH SUMMIT 2021 - Thoyyibah; Muyassaroh (English Language Teaching Journal, 2022)
The aim of this study is to describe the types of speech errors, the frequency of errors, and the causes of Speech Eerrors of Girl Environment Activistâ€™s Speech in Plastic Health Summit 2021. The type of this research is qualitative. The data are the utterances containing speech errors. The data was collected from videos watched on the plastic soup foundation YouTube account entitled Plastic Health Summit 2021 - Ms. Aeshnina Azzahra Aqilani (Nina), with a duration of 7:38 (seven minutes and thirty-nine seconds). The researcher finds six types of speech errors based on the theory of Clark and Clark. There are 28 speech errors uttered by Aeshnina Azzahra Aqilani with the frequencies as follows: silent pause (eleven times), filled pause (nine times), retraced false start (three times), repeats and interjections (two times), and stutters (one time). There are three causes: cognitive difficulty, anxiety, and social reason, this is caused by the occasional lack of concentration while the speakers say, and their concentration being hampered by the surrounding environment. There are many speech errors committed by Aeshnina Azzahra Aqilani which mean that she needs to increase her ability to deliver her speech smoothly and clearly. Keywords: Linguistics, Psycholinguistics, Speech errors Â